The unfavorable effects of COVID‐19 on Dutch advanced melanoma care. Issue 5 (22nd October 2021) - van Not, Olivier J.; van Breeschoten, Jesper; van den Eertwegh, Alfonsus J. M.; Hilarius, Doranne L.; De Meza, Melissa M.; Haanen, John B.; Blank, Christian U.; Aarts, Maureen J. B.; van den Berkmortel, Franchette W. P. J.; de Groot, Jan Willem B.; Hospers, Geke A. P.; Ismail, Rawa K.; et al.
Abstract: The COVID‐19 pandemic had a severe impact on medical care. Our study aims to investigate the impact of COVID‐19 on advanced melanoma care in the Netherlands. We selected patients diagnosed with irresectable stage IIIc and IV melanoma during the first and second COVID‐19 wave and compared them with patients diagnosed within the same time frame in 2018 and 2019. Patients were divided into three geographical regions. We investigated baseline characteristics, time from diagnosis until start of systemic therapy and postponement of anti‐PD‐1 courses. During both waves, fewer patients were diagnosed compared to the control groups. During the first wave, time between diagnosis and start of treatment was significantly longer in the southern region compared to other regions (33 vs 9 and 15 days, P ‐value <.05). Anti‐PD‐1 courses were postponed in 20.0% vs 3.0% of patients in the first wave compared to the control period. Significantly more patients had courses postponed in the south during the first wave compared to other regions (34.8% vs 11.5% vs 22.3%, P ‐value <.001). Significantly more patients diagnosed during the second wave had brain metastases and worse performance status compared to the control period. In conclusion, advanced melanoma care in the Netherlands was severely affected by the COVID‐19 pandemic. In the south, the start of systemic treatment for advanced melanoma was more often delayed, and treatment courses were more frequently postponed. During the second wave, patients were diagnosed with poorer patient and tumor characteristics. Longer follow‐up is needed to establish the impact on patient outcomes. Abstract : What's new? Little is known about the effects of COVID‐19 on advanced melanoma care. In this study, the authors examined several quality indicators of care. They observed a worsening in baseline characteristics, longer time between diagnosis and start of treatment and more postponed anti‐PD‐1 antibody courses with differences between the northern, middle and southern regions. Future studies are necessary to assess the long‐term consequences of our observed changes in advanced melanoma care.